KEBIJAKAN PENGEMBANGAN DAN PEMBERDAYAAN LEMBAGA KOMUNIKASI SOSIAL KELOMPOK INFORMASI MASYARAKAT - Mulyono Yalia; Noneng Sumiaty (Dialektika, 2019)
The main focus of this research is the development of policy implementation and empowerment of institutions of social communication (KIM) in the district of West Java Cirebon City. Restrictions issues identified as follows: (1) How is the implementation of government policy in the empowerment of social communication media in Cirebon City of West Java; (2) What factors are supporting and inhibiting the implementation of government policy in the empowerment of institutions of social communication (KIM) in the district of Cirebon City, West Java; (3) Measures are implemented by the Office of Communications and Information Provincial / District / City in realizing the government's policy in the empowerment of social communication in public institutions. The research method used in this study is a qualitative method of data collection techniques through participant observation and in-depth interviews. Based on the results that in the implementation of government policy on the development and empowerment of institutions of social communication in the district of West Java Cirebon City through approach of policy implementation factors found another dimension, namely the importance of supervision and coordination.